2017
DOI: 10.21548/38-2-2079
|View full text |Cite
|
Sign up to set email alerts
|

Application of Volatile Compounds Analysis for Distinguishing between Red Wines from Poland and from Other European Countries

Abstract: Authenticity and the geographical origin of wines are terms of great importance for consumers and producers. This work is focused on distinguishing between red wines from Poland and from other European countries, notably France, Italy and Spain. To achieve this goal, we determined aroma compounds in wines from different countries by headspace solid-phase microextraction/gas chromatography-mass spectrometry. The content of hexan-1-ol in Polish wines was significantly higher (about twice as high) than in French,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Ziółkowska et al (2016) applied LDA to the differentiation of white and red wines according to their geographical origin, based on volatile composition (determined by SPME/GC/MS) and they reported that the best discrimination among samples was obtained using hexanol (or hexan‐1‐ol) and phenylethyl alcohol (or 2‐phenyl ethanol), as well as ethyl decanoate and ethyl dodecanoate. Stój et al (2017) reported that the application of volatile compounds (determined by HS/SPME/GC/MS) and ANOVA, in combination with the Kruskal–Wallis test, resulted in statistically significant differences between French, Italian, Spanish and Polish red wines, based on their concentration of 3‐methylbutan‐1‐ol, hexanol (or hexan‐1‐ol), ( E )‐3‐hexen‐1‐ol, 3‐ethoxypropan‐1‐ol, butane‐2,3‐diol, phenylmethanol, 2‐phenylethanol, ethyl 2‐hydroxy‐4‐methylpentanoate, ethyl phenylacetate, 2‐phenylethyl acetate and 3‐(methylsulfanyl) propan‐1‐ol. The multiple comparisons test showed that hexanol efficiently distinguished Polish wines from those from other regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ziółkowska et al (2016) applied LDA to the differentiation of white and red wines according to their geographical origin, based on volatile composition (determined by SPME/GC/MS) and they reported that the best discrimination among samples was obtained using hexanol (or hexan‐1‐ol) and phenylethyl alcohol (or 2‐phenyl ethanol), as well as ethyl decanoate and ethyl dodecanoate. Stój et al (2017) reported that the application of volatile compounds (determined by HS/SPME/GC/MS) and ANOVA, in combination with the Kruskal–Wallis test, resulted in statistically significant differences between French, Italian, Spanish and Polish red wines, based on their concentration of 3‐methylbutan‐1‐ol, hexanol (or hexan‐1‐ol), ( E )‐3‐hexen‐1‐ol, 3‐ethoxypropan‐1‐ol, butane‐2,3‐diol, phenylmethanol, 2‐phenylethanol, ethyl 2‐hydroxy‐4‐methylpentanoate, ethyl phenylacetate, 2‐phenylethyl acetate and 3‐(methylsulfanyl) propan‐1‐ol. The multiple comparisons test showed that hexanol efficiently distinguished Polish wines from those from other regions.…”
Section: Resultsmentioning
confidence: 99%
“…To date, 700–800 aroma compounds have been identified in wine (Berger 2007, Villamor and Ross 2013), which provides strong evidence of its complex composition. Gas chromatography/MS is the analytical technique typically used for the identification of aroma compounds in wine, in combination with methodologies, such as headspace solid‐phase micro‐extraction (HS/SPME), and GC/olfactometry (López et al 2002, Escudero et al 2007, Li et al 2008, Tao et al 2008, Munoz‐Gonzalez et al 2011, Stój et al 2017). Volatile analysis has been used to verify the geographical origin of wine (Ziółkowska et al 2016, Stój et al 2017), the grape cultivar (Ziółkowska et al 2016), vintage (Zhang et al 2013), and to identify instances of wine fraud (Stój et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This type of investigation is also important in the context of fraud prevention in the oenological field. In research about the authenticity of red wines from Poland, Stoij et al [ 62 ] used HCA analysis to assess that the Polish wines were separated thoroughly from wines produced in other European countries, notably France, Italy, and Spain, starting from data on ethyl phenylacetate, hexan-1-ol, ethyl 2-hydroxy-4-methylpentanoate, (E)-3-hexen-1-ol, 2-phenylethanol and 3-(methylsulfanyl)propan-1-ol. Recently, Valentin et al [ 63 ] identified the chemical profile (including the volatile profile) that characterizes Chilean Carmérère wines by using HCA and PCA, starting to establish a database for further analysis of the authenticity of South American wines.…”
Section: Processing Of Hs-spme-gc-ms Data On Wine Volatiles By Multiv...mentioning
confidence: 99%
“…In order to prove the wine quality warranty for the consumer, numerous researchers studied the authenticity of a wine using labor-intensive and costly analyses which look for specific chemical features, such as elemental profile [8], isotopic fingerprints [9], and organic compounds (i.e., phenolic and volatile compounds, amino acids, sugars) [10,11,12,13] that can be related to geographical origin, varietal composition, or vintage year.…”
Section: Introductionmentioning
confidence: 99%